2021
DOI: 10.1097/rhu.0000000000001734
|View full text |Cite
|
Sign up to set email alerts
|

Role of Biological Agents in the Treatment of SARS-CoV-2–Associated Multisystem Inflammatory Syndrome in Children

Abstract: Objectives:The aims of this study were to evaluate the role of biological agents in the treatment of severe multisystem inflammatory syndrome in children (MIS-C) and to assess the current application, outcomes, and adverse effects in patients who are followed up in a pediatric intensive care unit (PICU).Patients and Methods: This observational, descriptive, medical records review study was performed on patients with MIS-C admitted to the PICU between September 1 and November 1, 2020. Through medical records re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…The median resolution day of the fever was 3 (1-10) days after anakinra treatment. The lymphocyte counts, BNP, CRP, and D-dimer values of the patients became normal on the median day of 5 (1-18), 8.5 (5-53), 10 (1-33), and 11.5 (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), respectively. The pattern of improvement in EF…”
Section: Outcome and Safetymentioning
confidence: 94%
“…The median resolution day of the fever was 3 (1-10) days after anakinra treatment. The lymphocyte counts, BNP, CRP, and D-dimer values of the patients became normal on the median day of 5 (1-18), 8.5 (5-53), 10 (1-33), and 11.5 (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), respectively. The pattern of improvement in EF…”
Section: Outcome and Safetymentioning
confidence: 94%
“…Significant increases in lymphocyte and platelet counts and significant decreases in ferritin, BNP and troponin levels were observed at the end of the first week of treatment in patients who were given biological therapy. 23 In addition, studies have emphasised the efficacy of anakinra in adult patients with SARS-CoV-2-associated hyperinflammatory conditions. 20 After treatment with anakinra, the need for vasopressors decreased and respiratory function improved significantly in eight patients with SARS-CoV-2-associated pneumonia who were followed up in the intensive care unit.…”
Section: Severe Manifestations* Criteria Met For Kdmentioning
confidence: 99%
“…A male dominance among the patients was shown in several studies. [10][11][12] A systematic review evaluating 917 MIS-C patients showed that the median age of the patients was 9.3 years, and 56.8% of the cases were males. 13 Similarly, male/female ratio was 1.37:1, and the median age was 7.5 years in another systematic review including 992 MIS-C patients.…”
Section: Epidemiologymentioning
confidence: 99%